Exploring the interplay: aspirin therapy, genetic polymorphisms, and homocysteine levels in cardiovascular disease patients / Siti Suraya Maisarah Abdul Sahar ... [et al.] - Abdul Sahar, Siti Suraya Maisarah; Sf Salim, Safreeda; Mohamad, Mohamad Iqhbal Kunji; Mohd Mokhtar, Mohd Amin; Rofiee, Mohd Salleh; Kek, Teh Lay; Salleh, Mohd Zaki; James, Richard Johari (Faculty of Pharmacy, 2024)
Cardiovascular disease (CVD) is a significant worldwide health threat expected to cause 23.6 million deaths annually by 2030. Homocysteine is an amino acid that is generated during the breakdown of methionine. Elevated levels of homocysteine are recognised as a standalone risk factor for cardiovascular disease, such as coronary artery disease and stroke. Methylenetetrahydrofolate reductase (MTHFR) and methionine synthase (MS) play essential roles in regulating homocysteine levels and maintaining cardiovascular health. The C677T (rs1801133) mutation of the MTHFR gene is closely linked to coronary artery disease due to decreased enzyme activity while the A2756G mutation (rs1805087) in the MS gene disrupts the remethylation process and is linked to elevated homocysteine levels and a higher risk of cardiovascular disease. Aspirin is a key treatment for cardiovascular disease by preventing platelet activation and aggregation, reducing the likelihood of blood clot formation. In addition, aspirin usage seems to be connected to homocysteine levels in persons dealing with CVD. The precise interplay between aspirin therapy, genetic polymorphisms, and their collective impact on homocysteine levels in CVD patients remains unclear. Therefore, this investigation aims to explore the effects of genetic polymorphisms (MTHFR and MS genes) and aspirin therapy on homocysteine levels in CVD patients from two hospitals in Selangor, Malaysia. Blood samples from 52 patients were collected and analysed, with homocysteine levels quantified using LCMS-QQQ, aspirin abundance determined through LCMS-QTOF, and genetic polymorphisms of MTHFR and MS genes identified using RT-PCR. Interestingly, individuals with CVD exhibiting elevated homocysteine levels did not show the mutant genotype for neither MTHFR nor MS genes. Furthermore, the potential influence of aspirin therapy emerged as a plausible explanation for the observed lower homocysteine levels in these patients. Other variables than genetic predisposition may play a role in causing elevated homocysteine levels in people with CVD. Our findings suggest that aspirin therapy may have a potential impact on reducing homocysteine levels in these patients. However, more research is needed to understand the underlying mechanisms.